Agri-Business Incubation for Rice-Based Ecosystems - Kumar, G A K; Krishna, R S; Pathak, H; Patra, B C; Sahu, R K; Mukherjee, A K; Mondal, B; Guru, P K; Borkar, N T; Rout, C; Das, A; Parida, S (Indian Farming, 2020)
In situations where rice cultivation is less remunerative, it can be made profitable through innovative agribusiness approaches. The role of Agribusiness Incubation Centre at NRRI is to make available the scalable and commercial technologies in rice based ecosystem to the budding agripreneurs to make their farming remunerative. With the above mentioned technologies and also with the upcoming technologies, ABI Centre would reach more number of aspirants and train them to develop agribusiness ventures through incubation process.